Multi-drug Resistant Tuberculosis in Rajshahi District - Hussain, M Wasim; Haque, M Azizul; Ekram, ARM Saifuddin; Hossain, Maruf; Rahman, M Fazlur (TAJ: Journal of Teachers Association, 2009)
Multidrug-resistant tuberculosis (MDR TB) is a form of tuberculosis that is resistant to at least INH and rifampicin. Total 4390 new patients with sputum smear positive pulmonary tuberculosis were enrolled in this study and treated with 2HRZE /6HT or HE. 3908 patients were cured and 482 patients had to undergo retreatment because of relapse or treatment failure. Retreatment was done with 2HRZES/1HRZE/5H3R3E3. Directly observed therapy was employed to treat all the cases. 18 patients remained sputum smear positive after eight months of treatment. So, the percentage of MDR TB in total study population was observed to be 0.4%.And the percentage of MDR TB among retreatment cases were 3.7%. doi: 10.3329/taj.v18i2.3190 TAJ 2005; 18(2): 113-117